Genotipagem e perfil de resistência aos antiretrovirais do virus da imunodeficiência tipo 1 em população com falha terapeutica no Ceará, Brasil : 2002 a 2004 - Medeiros, Melissa Soares (2006)
Genotypic testing for HIV-1 drug resistance is useful for selecting antiretroviral drugs for patients developing treatment failure. O melhor entendimento da sua interpretação facilitará sua utilização como ferramenta médica na terapêutica do HIV. The optimal understanding of its interpretation will give an important tool for HIV treatment. Objective: To identify common combinations of resistance mutations and antiretroviral resistance profile. Methods: Between April 2002 and March 2004, 101 protease and reverse transcriptase (RT) sequences were determined for HIV-1 isolates from patients who were failing antiretroviral therapy. Resistance profile was obtained by Stanford program. Results: male were 76.2%, median age 38 years, CD4 media was 279.21 cells/mm3 and Viral load 4.49 log. Total of 31 mutational patterns were detected to protease inhibitor (IP), 49 to nucleoside RT inhibitor (NRTI), and 17 to nonnucleoside RT inhibitor (NNRTI). K65R was detected in 5.9% isolates. The most frequent mutations were L90M, M184V and K103N to IP, NRTI and NNRTI respectively. The main mutational patterns accounted for 49% of mutant sequences to IP, 38.5% to ITRN accounted and 40,9% to NNRTI. Patients with three or more therapeutic failure had worst resistance profile to all IP except for Lopinavir, and NRTI except for Tenofovir. High resistance to Lamivudine and NNRTI were independent of failure quantity. Conclusion: The best susceptibility was found to Lopinavir at IP’s class and to Tenofovir at ITRN’s. The main mutational patterns to IP, ITRN and NNRTI represented almost half of all patterns found.